6m (m+2) = 0 is the factored form
m=0, m=-2 is m
Steps are on paper
If you need more explanation, comment
Answer:
(7/4)(2)(2)=7
Step-by-step explanation:
Answer:
510
Step-by-step explanation:
(0.68)750
shift decimal places
510.00
refine:510
In order to do these, simply translate the sentence mathematically.
1) x-15=7
2)3x+4=13
3)x+x+2+x+4=51
Hope this helped :D. Comment below if you have any questions!
Answer:
g(x) = x^2 -6x +9
Step-by-step explanation:
A function f(x) translated right h units and up k units will become ...
g(x) = f(x -h) +k
You want the function f(x) = x^2 to be translated right h=3 units, so it will become ...
g(x) = f(x -3) = (x -3)^2
g(x) = x^2 -6x +9